2016
DOI: 10.5020/18061230.2016.p334
|View full text |Cite
|
Sign up to set email alerts
|

Resultados da avaliação da cultura de segurança em um hospital público de ensino do Ceará

Abstract: Avaliar as dimensões da cultura de segurança do paciente de um hospital público de ensino, identificando suas áreas fortes e frágeis. Métodos: Estudo observacional, seccional, quantitativo, realizado entre dezembro de 2014 e janeiro de 2015, através da aplicação da versão adaptada para o português do questionário Hospital Survey on Patient Safety Culture (HSOPSC) com funcionários de um hospital de referência de Fortaleza, Ceará, Brasil. A análise dos resultados ocorreu por meio do cálculo dos valores absolutos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…These findings are consistent with national 18,24,27,32 and international 34,37 studies and indicate the need for actions to promote the notification of adverse events and to reduce the perception of consequent punishment, by means of concrete and continuous actions. They also show the importance of advancing in the promotion of a fair culture, with the support of institutional leaderships, including those of the associations that represent professional classes.…”
Section: /17supporting
confidence: 84%
See 2 more Smart Citations
“…These findings are consistent with national 18,24,27,32 and international 34,37 studies and indicate the need for actions to promote the notification of adverse events and to reduce the perception of consequent punishment, by means of concrete and continuous actions. They also show the importance of advancing in the promotion of a fair culture, with the support of institutional leaderships, including those of the associations that represent professional classes.…”
Section: /17supporting
confidence: 84%
“…Although the increasing perception related to staffing at the institution under study is acknowledged, it was observed that the percentage of positive answers of this dimension remained among the worse evaluated for period II (39.2%; n=62). A study conducted in the Brazilian Northeast region obtained a lower rate (36%; n=46) 24 as well as in Asian hospitals located in Saudi Arabia (33.8%;n=876). 22 Conversely, the percentage of positive answers of this dimension was lower than those found in a hospital in southern India, with 59.7% of positive answers.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Patient safety, a significant component of delivering quality care in health services, involves individual and organizational behaviors based on beliefs and targets with the aim of reducing medical errors to an acceptable level [4]. Effective communication, teamwork, motivative working conditions, and leadership in health care services support a culture of patient safety and contribute to the adoption of preventive measures, institutional learning, and the elimination of punishment as a means of error prevention [5]. Attention to patient safety by nurses within the health care team is a significant and necessary role in recovery and the development of a quality health care environment [6].…”
Section: Introductionmentioning
confidence: 99%